Assessment of open versus closed method of pneumoperitoneum creation in laparoscopic surgery (Journal of Pharmaceutical Negative Results, 2022)
Background: The concept of open laparoscopy is to eliminate the risks associated with blind insertion of the Veress needle and trocar. The present study was conducted to assess open versus closed method of pneumoperitoneum creation in laparoscopic surgery.Materials & Methods: 74 patients who underwent operative procedure for laparoscopysurgery of both genderswere divided into 2 groups based on method used. Group I patients were of open laparoscopy (Hasson technique) and group II were of Veress needle (closed method). Per operative findings like method of pneumoperitoneum creation and its duration, multiple attempts, incision size, extraperitoneal insufflation, port site bleeding, gas leak, total gas used were recorded. Results: out of 74 patients, males were 46 and females were 28. In group I and group II, the mean size of incision (mm) was 11.2 and 10.4, duration of pneumoperitonium creation (Sec) was 104.2 and 138.4, multiple attempts were seen in 9 and 4, gas leak at port site in 7and 3, port site bleeding in 5 and 2, pre peritoneal insufflation in 0 and 1 and wound infection in 1 and 2 respectively. The difference was significant (P< 0.05).Conclusion: Both methods were comparable interms of time taken to complete the operation and major and minor complications. Thus, open and closed methods of creating pneumoperitoneum in laparoscopic surgery are safe to perform.